Comparison of protocols for determining the subtalar joint angle - Tartaruga, MP; Cadore, EL; Alberton, CL; Nabinger, E; Tartaruga, LAP; Ávila, AOV; others (Acta Ortop Bras.[online]. 2010; 18 (3): 122-6. Available from URL: http://www. scielo. br/aob, 2010)
n/a
n/a